Chronic effects of stretching on range of motion with consideration of potential moderating variables: A systematic review with meta-analysis - Andreas Konrad; Shahab Alizadeh; Abdolhamid Daneshjoo; Saman Hadjizadeh Anvar; Andrew Graham; Ali Zahiri; Reza Goudini; Chris Edwards; Carina Scharf; David George Behm (Elsevier, 2024)
Background: It is well known that stretch training can induce prolonged increases in joint range of motion (ROM). However, to date more information is needed regarding which training variables might have greater influence on improvements in flexibility. Thus, the purpose of this meta-analysis was to investigate the effects of stretch training on ROM in healthy participants by considering potential moderating variables, such as stretching technique, intensity, duration, frequency, and muscles stretched, as well as sex-specific, age-specific, and/or trained state-specific adaptations to stretch training. Methods: We searched through PubMed, Scopus, Web of Science, and SportDiscus to find eligible studies and, finally, assessed the results from 77 studies and 186 effect sizes by applying a random-effect meta-analysis. Moreover, by applying a mixed-effect model, we performed the respective subgroup analyses. To find potential relationships between stretch duration or age and effect sizes, we performed a meta-regression. Results: We found a significant overall effect, indicating that stretch training can increase ROM with a moderate effect compared to the controls (effect size = -1.002; Z = -12.074; 95% confidence interval: -1.165 to -0.840; p < 0.001; I2 = 74.97). Subgroup analysis showed a significant difference between the stretching techniques (p = 0.01) indicating that proprioceptive neuromuscular facilitation and static stretching produced greater ROM than did ballistic/dynamic stretching. Moreover, there was a significant effect between the sexes (p = 0.04), indicating that females showed higher gains in ROM compared to males. However, further moderating analysis showed no significant relation or difference. Conclusion: When the goal is to maximize ROM in the long term, proprioceptive neuromuscular facilitation or static stretching, rather than ballistic/dynamic stretching, should be applied. Something to consider in future research as well as sports practice is that neither volume, intensity, nor frequency of stretching were found to play a significant role in ROM yields.